Study on the effect of waveform film holes on film cooling efficiency - Qian, Cheng; Wang, Mingwei; Yang, Weihua; Liu, Yuang; Zhang, Beixuan (Frontiers in Energy Research, 2023)
In order to improve the film cooling efficiency of the cooling gas on the hot side wall of the plate, the flow field, temperature field and the average film cooling efficiency of the cylindrical hole, rectangular hole and waveform hole near the wall were compared and analyzed by numerical calculation method. Compared with cylindrical holes, the average spanwise film cooling efficiency of rectangular hole is improved by 100%, and the average spanwise film cooling efficiency of waveform hole is improved by 130%. In addition, the effects of the amplitude A of the waveform hole and the initial phase ϕ on the cooling efficiency are compared and analyzed. The results show that: Within the scope of this study, when the blowing ratio M = 1, lifting the initial phase ϕ of the waveform hole can effectively improve the film cooling efficiency of the cooling gas on the wall. When the amplitude A of the waveform hole is raised, the film cooling efficiency of the cooling gas on the wall will first increase and then decrease, reaching the maximum at the amplitude A = 0.4D. At low blowing ratio, the geometric structure of waveform hole has little influence on the cooling effect of wall surface. Under high blowing ratio, when the geometric structure of waveform hole is changed, the influence of secondary flow on the average spanwise cooling efficiency of wall surface is great.